Surface modification of cellulosic fibres for multi-purpose TiO(2) based nanocomposites - Goncalves, Gil (2009)
Vegetable cellulose fibres have been surface modified using the hydrolysis of tetraethoxysilane (TEOS), octyltrimethoxysilane (OTMS) or phenyltrimethoxysilane (PTMS), followed by the layer-by-layer deposition of previously synthesized TiO2 nanoparticles. Raman, FTIR and 29Si Solid State NMR spectroscopies, and SEM were used to characterize the resulting nanocomposites. Water contact angle measurements were performed and the results indicate a quite distinct behaviour depending on the employed surface modification procedure. We anticipate that some of the cellulose-based composite materials have potential to be used in self-cleaning surfaces and reinforcing agents in polymer matrices, namely due to their hydrophobic surface and photostability when exposed to solar radiation.